Ethnolinguistic Study of Tontemboan Language Expressions in Sende'eng Traditional Cooking by The Lower Tombasian Village Community - Jusuf Daniel Ondang; Fergina Lengkoan; Tirza A. Kumayas; Fivy A. Andries; Anas Irwan (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
This activity explores the ethnolinguistic aspects of Tontemboan language expressions in cooking sende'eng in the community of Tombasian Bawah Village. Using a qualitative ethnolinguistic approach, this activity reveals that variations in ingredients, cooking methods, and food presentation are not only culinary choices, but also carry linguistic meanings that reflect the mindset and cultural identity of the community. These findings demonstrate how traditional cooking practices serve as a means to preserve and convey cultural heritage. This activity also emphasizes the importance of language in expressing the cultural values and traditions of the community. By documenting these linguistic expressions, this activity provides insight into the cultural significance of sende'eng and its role in the community of Tombasian Bawah Village. In addition, this activity highlights the importance of maintaining minority languages through documentation and research such as this. In the context of cooking sende'eng, Tontemboan language expressions play a key role in communicating cooking techniques, ingredients, and philosophies that are passed down from generation to generation. This activity contributes to a deeper understanding of the relationship between language, culture, and food, showing how traditional cooking practices serve as a medium to preserve and convey cultural heritage.